The Brownfield of Padurea Neagra (Crisul Repede Valley) - Rodica PETREA; Dănuţ PETREA; Valentin NEMEŞ (Transylvanian Review of Administrative Sciences, 2011)
The presence and management of abandoned industrial sites (brownfields), which cover large areas of land in the Crişul Repede Valley Territorial Planning Unit, is a great challenge. Of the many abandoned industrial sites, the glass factory of Pădurea Neagră was selected in order to highlight the peculiarities of a certain typology of territorial occupation and use, which is representative for the studied area. The whole abandoned area was reserved entirely for the glass factory, which now finds itself in an advanced stage of degradation. As a peculiarity, one remarks that it is surrounded by the neighboring secondary homes, an area in full expansion. The industrial zone covers a significant part of the built-up area of the village (21%), preventing the development of the territory in question, while at the same time it creates an aesthetic disability for the small community which has only the perspective of tourism development. The revitalization of the community can be achieved through the rehabilitation/conversion of the industrial area, as a valid alternative to the inevitable urban expansion, as it will have a positive impact on the development of tourism. There are many uses which could be gained as a result of the rehabilitation, but the most appropriate use would be a multifunctional center of creation, accompanied by a small glass museum and a workshop that would produce small-scale traditional glasswork, for tourism purposes.